Infantile Spasms, Hypsarrhythmia, and Adrenoleukodystrophy (ALD) - J Gordon Millichap (Pediatric Neurology Briefs)
An 8 1/2 month-old girl with seizures beginning at 5 days, hypsarrhythmia in the EEG, severe retardation, and a clinical diagnosis of infantile spasms was discovered to have biochemical and pathological features of adrenoleukodystrophy, as reported from the John F. Kennedy Institute, Johns Hopkins University, Baltimore, Maryland.